(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article describes the causes of dyslalia, diagnosis of dyslalia and step-by-step treatment methods, methods of eliminating dyslalia, and conclusions and suggestions on the topic. Dyslalia is a violation of sound pronunciation during the preserved innervation of the normal auditory and speech apparatus.